RNA Sequencing Reveals Key Metabolic Pathways Are Modified by Short-Term Whole Egg Consumption - Bries, Amanda E.; Webb, Joe L.; Vogel, Brooke; Carrillo, Claudia; Day, Timothy A.; Kimber, Michael J.; Valentine, Rudy J.; Rowling, Matthew J.; Clark, Stephanie; Schalinske, Kevin L.; McNeill, Elizabeth M. (Frontiers in Nutrition, 2021)
Eggs are protein-rich, nutrient-dense, and contain bioactive ingredients that have been shown to modify gene expression and impact health. To understand the effects of egg consumption on tissue-specific mRNA and microRNA expression, we examined the role of whole egg consumption (20% protein, w/w) on differentially expressed genes (DEGs) between rat (n =12) transcriptomes in the prefrontal cortex (PFC), liver, kidney, and visceral adipose tissue (VAT). Principal component analysis with hierarchical clustering was used to examine transcriptome profiles between dietary treatment groups. We performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis as well as genetic network and disease enrichment analysis to examine which metabolic pathways were the most predominantly altered in each tissue. Overall, our data demonstrates that whole egg consumption for 2 weeks modified the expression of 52 genes in the PFC, 22 genes in VAT, and two genes in the liver (adj p < 0.05). Additionally, 16 miRNAs were found to be differentially regulated in the PFC, VAT and liver, but none survived multiple testing correction. The main pathways influenced by WE consumption were glutathione metabolism in VAT and cholesterol biosynthesis in the PFC. These data highlight key pathways that may be involved in diseases, may be impacted by acute consumption of a diet containing whole eggs.